The Importance of Leadership Management in Fundraising Zakat - Syahputra, Angga; Khairina, Khalish (Madania: Jurnal Kajian Keislaman, 2021)
Zakat is a large scope of financial potential in Islam which has a very broad impact if it is properly optimized and managed. For that, it takes not only a leader figure but also a person who has leadership in maximizing zakat fundraising. This study aims to see the role of leadership in zakat fundraising using qualitative research methods. The type of research used is literature review by exploring relevant sources obtained from previous research, books, journals and trusted websites. This research shows that leadership has a very important role in the fundraising of zakat. With good leadership, a good system will also be built in various aspects of zakat fundraising. In a larger scope, it takes the role of the government as the main leader in zakat fundraising. The presence of the government with various potentials and good leadership will be able to optimize the receipt of zakat funds. Zakat merupakan scope besar potensi keuangan dalam Islam yang memiliki dampak sangat luas jika dioptimalkan dan dikelola dengan baik. Untuk itu, dibutuhkan tidak hanya sosok leader tetapi personal yang memiliki leadership dalam memaksimalkan fundraising zakat. Penelitian ini bertujuan untuk melihat peran leadership dalam fundraising zakat dengan menggunakan metode penelitian kualitatif. Jenis penelitian yang digunakan adalah literatur review dengan mengeksplorasi sumber relevan yang didapatkan dari penelitian terdahulu, buku, jurnal maupun website terpercaya. Penelitian ini menghasilkan bahwa leadership memiliki peran yang sangat penting dalam fundraising zakat. Dengan leadership yang baik maka akan terbangun sistem yang baik pula dalam berbagai aspek fundraising zakat. Dalam cakupan yang lebih besar, dibutuhkan peran pemerintah sebagai leader utama dalam fundraising zakat. Kehadiran pemerintah dengan berbagai potensi yang dimiliki maupun kepemimpinan yang baik akan mampu mengoptimalkan penerimaan dana zakat.